2000
DOI: 10.1103/physrevb.61.14647
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in perovskite manganites with orbital degree of freedom

Abstract: Roles of orbital degree of freedom of Mn ions in phase transition as a function of temperature and hole concentration in perovskite manganites are studied. It is shown that the orbital order-disorder transition is of the first order in the wide region of hole concentration and the Néel temperature for the anisotropic spin ordering, such as the layer-type antiferromagnetic one, is lower than the orbital ordering temperature due to the anisotropy in the orbital space. The calculated results of the temperature de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The orbital ordered state is determined in the mean field approximation. 33 By applying the Holstein-Primakoff transformation to the spin operators, the dispersion relation of the spin wave is calculated. Experimentally, the spin wave in LaMnO 3 was measured by the neutron scattering experiments in Refs.…”
Section: Transition Temperatures and Spin Wave Dispersionmentioning
confidence: 99%
“…The orbital ordered state is determined in the mean field approximation. 33 By applying the Holstein-Primakoff transformation to the spin operators, the dispersion relation of the spin wave is calculated. Experimentally, the spin wave in LaMnO 3 was measured by the neutron scattering experiments in Refs.…”
Section: Transition Temperatures and Spin Wave Dispersionmentioning
confidence: 99%
“…We investigate the orbital states at the paramagnetic and A-AF phases by applying the mean field approximation. 25 A unit cell which includes four Mn sites is adopted. These Mn sites are termed A 1 , A 2 , B 1 and B 2 (see Fig.…”
Section: Orbital Wavementioning
confidence: 99%
“…4) Recent studies revealed that the DE scenario alone cannot explain the whole physics occurring in the manganite system and thereby the interplay among spin, charge, orbital, and lattice should be invoked to render more precise explanations on the CMR phnomenon. [5][6][7] It has been suggested that the magnetic polaron attributable to combined effect of lattice distortions and magnetic clusters is a probable origin of CMR effect, designating that short-range interactions is a crucial factor to be taken. 8) Recently, Dai et al investigated on the low-doped system La 1Àx Ca x MnO 3 (0:15 x 0:3) by means of neutron diffuse scattering technique, revealing that the short-range charge (polaron) couplings persist even in the low temperature regime and affect the electrical transport properties.…”
Section: Introductionmentioning
confidence: 99%